High-strength wear-resistant regenerated polyester for new energy vehicles and preparation method thereof
Patent Information
- Application Number
- CN202611392197.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-10-13
AI Technical Summary
[0009]针对现有再生聚酯强度不足、耐磨性差,难以满足新能源汽车高压线束保护套管使用要求的缺陷,本发明提供了一种新能源汽车用的高强耐磨再生聚酯和制备方法
本发明提供的高强耐磨再生聚酯,通过巯基-烯点击反应将双键改性二氧化硅以C-S共价键接枝到聚酯分子链上,使二氧化硅分散并牢固结合于表面和基体中,在摩擦过程中作为硬质支撑点抵抗磨损且不易脱落;同时均苯四甲酸二酐在熔融共混阶段对废旧聚酯分子链进行扩链修复,恢复分子量。两者协同作用,使纤维断裂强度、编织套管耐磨次数等综合性能优于常规再生聚酯,满足新能源汽车高压线束编织套管对强度和耐磨的要求。本发明以废旧聚酯为原料,通过化学键合增强以及扩链修复的双重机制,实现废旧聚酯的再利用,具有良好的经济效益和环境效益。
Smart Images

Figure SMS_5
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polyester polymer technology, and relates to a high-strength, wear-resistant recycled polyester for new energy vehicles and its preparation method. Background Technology
[0002] Polyester is widely used in the textile sheathing field due to its excellent mechanical properties, heat resistance, and dimensional stability. The rapid development of the new energy vehicle industry has placed higher performance requirements on high-voltage wiring harness protective sheaths. They not only need to have excellent abrasion resistance and high strength, but also good air permeability and heat dissipation performance to ensure the long-term stable operation of high-voltage wiring harnesses in compact spaces.
[0003] Recycled polyester, mainly produced from recycled PET bottles or flakes through washing, crushing, melt granulation, and spinning, has become an important direction for the green transformation of the textile industry. However, existing recycled polyester still faces many technical bottlenecks when applied to high-voltage wiring harness protective sleeves in new energy vehicles.
[0004] First, recycled polyester generally has low strength. During the repeated melting and processing of recycled PET bottle flakes, the polyester molecular chains undergo thermal degradation, leading to a decrease in the degree of polymerization and a wider molecular weight distribution. The fiber breaking strength is even difficult to reach 2.5 cN / dtex, which is insufficient to meet the tensile strength requirements of high-voltage wire harness protective sleeves.
[0005] Secondly, the abrasion resistance of existing recycled polyester is insufficient. High-voltage wiring harnesses in new energy vehicles are continuously subjected to vibration, friction, and bending stress during vehicle operation. The abrasion resistance of the protective sleeve directly affects the safety and service life of the high-voltage circuit. T / SGX 015-2022, "Self-winding Protective Sleeves for Wiring Harnesses - Part 1: New Energy Vehicles," clearly stipulates that the abrasion resistance should be greater than 2000 cycles (reciprocating friction). Sleeves braided from conventional recycled polyester often fail to consistently meet this standard due to insufficient surface hardness and weak monofilament strength, posing a safety hazard.
[0006] Third, the breathability and heat dissipation performance of recycled polyester fibers need to be improved. High-voltage wiring harnesses in new energy vehicles carry high voltage and high current, and the wiring harnesses generate significant heat. If the protective bushings have poor breathability and heat dissipation, heat will accumulate and accelerate the aging of the insulation layer.
[0007] In the prior art, CN117904745A discloses a method for preparing functionalized silanes for polyester modification by reacting vinyltrichlorosilane with cashew phenol, but it mainly targets antibacterial functions; CN120382704A discloses cyclotriphosphazene-modified silane coupling agents for flame retardancy; CN105696306A discloses a method for grafting hydrophobic monomers onto the surface of PET fabrics after thiolization, but it does not involve high strength and high abrasion resistance targets.
[0008] There is a need to develop a recycled polyester that combines high strength, excellent wear resistance, good breathability and heat dissipation properties, so that it can meet the requirements for use in high-voltage wiring harness braided sleeves for new energy vehicles. Summary of the Invention
[0009] To address the shortcomings of existing recycled polyesters, such as insufficient strength and poor abrasion resistance, which make it difficult to meet the requirements for high-voltage wiring harness protection sleeves in new energy vehicles, this invention provides a high-strength, abrasion-resistant recycled polyester for new energy vehicles and its preparation method.
[0010] The objective of this invention can be achieved through the following technical solutions: In a first aspect, the present invention provides a high-strength, wear-resistant recycled polyester, wherein the raw materials for preparing the recycled polyester include mercapto-modified polyester, pyromellitic dianhydride, and double bond-modified silica. The mercapto-modified polyester is obtained by modifying waste polyester with a mercaptosilane coupling agent; The double-bond modified silica is obtained by reacting nano-silica modified with an aminosilane coupling agent with an epoxy-containing vinylsilane intermediate; the epoxy-containing vinylsilane intermediate is obtained by reacting vinyltrichlorosilane with glycidol.
[0011] Waste polyester refers to polyester raw materials obtained from recycled polyethylene terephthalate (PET) bottle flakes, PET packaging materials, or PET textile waste after washing, crushing, and drying. In this invention, waste polyester mainly refers to recycled PET bottle flakes.
[0012] Preferably, the mass ratio of the mercapto-modified polyester to the double bond-modified silica is 100:1-2.
[0013] The method for preparing the double bond modified silica includes: (a) Preparation of amino-modified silica: Silica was dispersed in an ethanol / water mixture (volume ratio 4:1), and γ-aminopropyltriethoxysilane (KH-550) was added at a mass ratio of 5% to silica. The mixture was stirred at 75-80℃ for 6-8 hours. After the reaction was completed, the mixture was centrifuged, washed three times with anhydrous ethanol, and dried under vacuum at 80℃ for 12 hours to obtain amino-modified silica.
[0014] After the ethoxy group of KH-550 is hydrolyzed, it condenses with the hydroxyl group on the surface of silica to form Si-O-Si bonds, introducing amino groups into the silica surface and providing active sites for subsequent reactions with epoxy groups.
[0015] The structure of amino-modified silica is as follows: .
[0016] (b) Synthesis of epoxy-containing vinylsilane intermediates: Under nitrogen protection, vinyltrichlorosilane was dissolved in anhydrous tetrahydrofuran, and triethylamine was added as an acid-binding agent. The mixture was then cooled to 0°C. Glycidyl ether (in a molar ratio of 3.1:1 to vinyltrichlorosilane) was slowly added dropwise. After the addition was complete, the mixture was allowed to rise to room temperature and reacted for 4–6 hours. After the reaction was complete, the triethylamine hydrochloride was removed by filtration, and the solvent was removed by vacuum distillation to obtain an epoxy-containing vinylsilane intermediate.
[0017] The epoxy-containing vinylsilane intermediate molecule contains three epoxy groups, which can form multi-point covalent grafts with amino groups. Compared with single-point grafting, multi-point grafting allows nano-silica to be anchored to the polyester molecular chain through multiple chemical bonds, forming a more effective stress transfer network at the interface. When the material is subjected to external forces, the stress can be dispersed and transferred through multiple grafting points, avoiding stress concentration on a single chemical bond, thereby improving the interfacial bonding strength and mechanical stability.
[0018] The structure of the epoxy-containing vinylsilane intermediate is as follows: .
[0019] (c) Preparation of double bond modified silica: The intermediate obtained above was dispersed with amino-modified silica in anhydrous toluene and reacted under nitrogen protection at 60-80℃ for 6-8 h with stirring. After the reaction was completed, the mixture was separated, washed three times with toluene, and dried under vacuum at 80℃ for 12 h to obtain double-bond modified silica.
[0020] The epoxy groups of the epoxy-containing vinylsilane intermediate undergo a ring-opening addition reaction with the amino groups on the surface of amino-modified silica to form CN covalent bonds. Toluene, as an aprotic solvent, can effectively disperse silica and dissolve organic intermediates, promoting the heterogeneous reaction.
[0021] The chemical reaction formula for synthesizing double-bond modified silica is: .
[0022] Preferably, the mass ratio of the γ-aminopropyltriethoxysilane to the epoxy-containing vinylsilane intermediate is 1-2:1.
[0023] In a second aspect, the present invention provides a method for preparing high-strength, abrasion-resistant recycled polyester as described in the first aspect, comprising the following steps: (1) Place the waste polyester in an ethanol / water solution containing 0.5-2% by mass of 3-mercaptopropyltriethoxysilane or 3-mercaptopropyltrimethoxysilane and react at 60-80℃ for 2-4 h. After the reaction is complete, wash three times with anhydrous ethanol and dry under vacuum at 60℃ for 6 h to obtain mercapto-modified polyester.
[0024] In this step, the ethoxy group of the mercaptosilane coupling agent hydrolyzes and condenses with the hydroxyl groups on the surface of the waste polyester to form Si-OC bonds, introducing mercapto groups (-SH) onto the polyester surface. These mercapto groups serve as active sites for subsequent click reactions.
[0025] (2) The mercapto-modified polyester was immersed in a toluene solution containing double-bond modified silica, and azobisisobutyronitrile (1-2% by mass of double-bond modified silica) was added under nitrogen protection. The temperature was raised to 75-85℃ and the reaction was carried out for 4-6 hours. After the reaction was completed, the polyester was removed and dried under vacuum at 60℃ for 12 hours to obtain the synthetic polyester.
[0026] Azobisisobutyronitrile (AIBN) decomposes at 75-85℃ to generate free radicals, which initiate a click addition reaction between the thiol group (-SH) and the carbon-carbon double bond (C=C) to form a CS covalent bond. This covalent bond grafts double-bonded modified silica onto the polyester molecular chain.
[0027] The mechanism of click addition reaction of mercapto-alkene is as follows: .
[0028] (3) Mix 100 parts of synthetic polyester, 0.3-0.8 parts of pyromellitic dianhydride, 0.5-1 parts of pentaerythritol stearate, and 0.1-0.3 parts of antioxidant at high speed for 20-30 minutes. Then, melt-blend and extrude the mixture at 250-265℃ using a compounding extruder. After water cooling, granulate the mixture to obtain recycled polyester chips. Melt and spray the recycled polyester chips at 270-290℃ in a spinning machine. Cool the chips with side air (15-20℃). Draft the chips to 2.0-2.4 times their original length (dragging temperature 200-230℃) in a drawing machine. Then, curl the fibers at 150-170℃, relax and heat-set them at 200-220℃, and cut them to obtain recycled polyester fibers.
[0029] Pyromellitic dianhydride is a tetrafunctional chain extender; its anhydride groups undergo a ring-opening reaction with the terminal hydroxyl / carboxyl groups of the polyester, reconnecting broken polyester molecular chains. Pentaerythritol stearate, as a processing aid, reduces melt viscosity and improves the dispersion uniformity of each component during melt blending. Antioxidants inhibit the thermal oxidative degradation of polyester during high-temperature processing.
[0030] Thirdly, the present invention provides an application of high-strength, wear-resistant recycled polyester as described in the first aspect in the braided sleeve of high-voltage wiring harnesses for new energy vehicles.
[0031] In this application, the high-strength, abrasion-resistant recycled polyester, after being doubling and warping, is woven into a self-winding sleeve on a high-speed circular loom, which can be used for external protection of high-voltage wiring harnesses in new energy vehicles. It can meet the requirement of abrasion resistance greater than 2000 cycles; simultaneously, the chemically bonded nano-silica in the fiber acts as a hard support point to resist wear during friction and is not easily detached, which is beneficial to the long-term stable operation of the high-voltage wiring harness under vehicle vibration conditions.
[0032] The beneficial effects of this invention are as follows: The high-strength, wear-resistant recycled polyester provided by this invention grafts double-bonded modified silica onto the polyester molecular chain via a mercapto-olefin click reaction, using CS covalent bonds. This disperses and firmly binds the silica to the surface and matrix, acting as a hard support point to resist wear and prevent detachment during friction. Simultaneously, pyromellitic dianhydride extends and repairs the waste polyester molecular chain during the melt blending stage, restoring its molecular weight. The synergistic effect of these two processes results in superior overall performance of recycled polyester, including fiber breaking strength and braided sleeve abrasion resistance, compared to conventional recycled polyester, meeting the strength and wear resistance requirements of high-voltage wiring harness braided sleeves for new energy vehicles. This invention utilizes waste polyester as raw material, achieving reuse through a dual mechanism of chemical bonding reinforcement and chain extension repair, resulting in significant economic and environmental benefits. Detailed Implementation
[0033] To further illustrate the technical means and effects of the present invention in achieving the intended purpose, the following detailed description of the specific implementation methods, structures, features and effects of the present invention, in conjunction with preferred embodiments, is provided below.
[0034] Example 1 A method for preparing high-strength, abrasion-resistant recycled polyester includes the following steps: (1) 100 parts of waste polyester were placed in 3000 parts of an ethanol / water solution containing 1% by mass of 3-mercaptopropyltriethoxysilane and reacted at 70°C for 3 h. After the reaction was completed, the mixture was filtered, washed three times with anhydrous ethanol, and dried under vacuum at 60°C for 6 h to obtain mercapto-modified polyester.
[0035] (2) The obtained mercapto-modified polyester and 1.5 parts of double bond-modified silica were immersed in toluene solution, and azobisisobutyronitrile (1.5% of the mass of double bond-modified silica) was added. The reaction was carried out at 80°C for 5 h under nitrogen protection. After the reaction was completed, the mixture was filtered and dried under vacuum at 60°C for 12 h to obtain the synthetic polyester.
[0036] (3) 100 parts of synthetic polyester, 0.5 parts of pyromellitic dianhydride, 0.5 parts of pentaerythritol stearate, and 0.2 parts of antioxidant (Irganox 1010) were mixed at high speed for 25 min. The mixture was then melt-blended and extruded at 255°C using a compounding extruder, and water-cooled and pelletized to obtain recycled polyester chips. The recycled polyester chips were melt-sprayed at 280°C in a spinning machine, cooled by side blowing (18°C), and drawn to 2.2 times their original size (drawing temperature 215°C) in a drawing machine. Subsequently, they were crimped at 160°C, relaxed and heat-set at 210°C, and cut to obtain recycled polyester fibers.
[0037] The preparation of double-bond modified silica includes: (a) Disperse 5 parts of silica in a mixed solvent of ethanol / water (volume ratio 4:1), add 0.25 parts of γ-aminopropyltriethoxysilane (KH-550), and stir at 78°C for 7 h. After the reaction is complete, centrifuge, wash 3 times with anhydrous ethanol, and dry under vacuum at 80°C for 12 h to obtain amino-modified silica.
[0038] (b) Under nitrogen protection, 1.0 part of vinyltrichlorosilane was dissolved in anhydrous tetrahydrofuran, and 2.2 parts of triethylamine were added. The mixture was cooled to 0°C. 1.4 parts of glycidyl ether was slowly added dropwise, and after the addition was complete, the mixture was allowed to react at room temperature for 5 hours. The remaining reactants were monitored by TLC. After the reaction was complete, the triethylamine hydrochloride was removed by filtration, and the solvent was removed by vacuum distillation to obtain an epoxy-containing vinylsilane intermediate. Infrared spectroscopy showed that at 912 cm⁻¹... -1 The characteristic absorption peak of the epoxy group appears nearby, at 1612 cm⁻¹. -1 The presence of a characteristic absorption peak near a carbon-carbon double bond indicates a successful reaction between vinyltrichlorosilane and glycidyl. Mass spectrometry analysis shows the molecular ion peak at m / z 275.1 [M+H]. + This is consistent with the theoretical molecular weight of the target product.
[0039] (c) 0.25 parts of the above-mentioned epoxy-containing vinylsilane intermediate were dispersed with amino-modified silica in anhydrous toluene and reacted at 70°C for 7 h under nitrogen protection. After the reaction was completed, the mixture was filtered, washed three times with toluene, and dried under vacuum at 80°C for 12 h to obtain double-bond modified silica. Infrared spectroscopy showed that at 1612 cm⁻¹... -1 The characteristic absorption peak of the carbon-carbon double bond is retained nearby, at 912 cm⁻¹. -1 The characteristic absorption peaks of the epoxy groups are retained in the vicinity.
[0040] Example 2 A method for preparing high-strength, abrasion-resistant recycled polyester includes the following steps: (1) 0.5% by mass of 3-mercaptopropyltrimethoxysilane, reacted at 60°C for 4 hours, and the rest were the same as in Example 1 (1).
[0041] (2) 2.0 parts of double bond modified silica, 1.0% AIBN, reacted at 75°C for 6 hours, and the rest were the same as step (2) in Example 1.
[0042] (3) 100 parts of synthetic polyester, 0.3 parts of pyromellitic dianhydride, 0.3 parts of pentaerythritol stearate, and 0.1 parts of antioxidant (Irganox 1010) were mixed at high speed for 20 min. The mixture was then melt-blended and extruded at 250°C using a compounding extruder, and water-cooled and pelletized to obtain recycled polyester chips. The recycled polyester chips were melt-blown out at 270°C in a spinning machine, cooled by side blowing (15°C), and drawn to 2.0 times their original size (drawing temperature 200°C) in a drawing machine. Subsequently, they were crimped at 150°C, relaxed and heat-set at 200°C, and cut to obtain recycled polyester fibers.
[0043] Example 3 A method for preparing high-strength, abrasion-resistant recycled polyester includes the following steps: (1) 2% by mass of 3-mercaptopropyltrimethoxysilane, reacted at 80°C for 2 hours, the rest is the same as step (1) in Example 1.
[0044] (2) 1.0 part of double bond modified silica, 2.0% AIBN, react at 85℃ for 4h, and the rest is the same as step (2) in Example 1.
[0045] (3) 100 parts of synthetic polyester, 0.8 parts of pyromellitic dianhydride, 0.8 parts of pentaerythritol stearate, and 0.3 parts of antioxidant (Irganox 1010) were mixed at high speed for 30 min. The mixture was then melt-blended and extruded at 265°C using a compounding extruder, and water-cooled and pelletized to obtain recycled polyester chips. The recycled polyester chips were melt-blown out at 290°C in a spinning machine, cooled by side blowing (20°C), and drawn to 2.4 times their original size (drawing temperature 230°C) in a drawing machine. Subsequently, they were crimped at 170°C, relaxed and heat-set at 220°C, and cut to obtain recycled polyester fibers.
[0046] Example 4 A method for preparing high-strength, abrasion-resistant recycled polyester includes the following steps: The procedure is basically the same as in Example 1, except that in step (c) of preparing double-bond modified silica, the amount of the epoxy-containing vinylsilane intermediate is 0.125 parts. The remaining steps and parameters are the same as in Example 1.
[0047] Comparative Example 1 The difference from Example 1 is that the waste polyester is not modified with mercapto groups and no double-bond modified silica is added. Recycled polyester is prepared by mixing 100 parts of waste polyester, 0.5 parts of pyromellitic dianhydride, 0.5 parts of PETS, and 0.2 parts of antioxidant.
[0048] Comparative Example 2 The difference from Example 1 is that pyromellitic dianhydride is not added. Recycled polyester is prepared by mixing 100 parts recycled polyester, 0.5 parts PETS, and 0.2 parts antioxidant.
[0049] Comparative Example 3 The difference from Example 1 is that the waste polyester is not modified with mercapto, and the double bond modified silica is directly physical blended without click reaction.
[0050] Comparative Example 4 The difference from Example 1 is that amino-modified silica replaces double-bond modified silica.
[0051] Comparative Example 5 The difference from Example 1 is that γ-methacryloyloxypropyltrimethoxysilane (KH-570) modified silica replaces double bond modified silica.
[0052] Modification steps: Disperse 5 parts of silica in a mixed solvent of ethanol / water (volume ratio 4:1), add 25 parts of KH-570, and stir at 78℃ for 7 h. Centrifuge, wash 3 times with anhydrous ethanol, and vacuum dry at 80℃ for 12 h to obtain KH-570 modified silica.
[0053] Performance testing: The recycled polyester obtained in the examples and comparative examples was braided into self-winding sleeves (braiding density 90%, nominal diameter 8 mm), and then the following performance tests were performed. The test results are shown in Table 1. Among them, fiber breaking strength and elongation at break can be tested directly, while the other items are tested on the braided sleeves.
[0054] 1. Breaking strength and elongation at break: The fiber was tested directly in accordance with GB / T 14344.
[0055] 2. Wear resistance of the casing: The wear resistance requirements are in accordance with the T / SGX 015-2022 standard, and the test is conducted according to the ISO 6722 standard.
[0056] 3. Breathability test: The test shall be conducted in accordance with GB / T 5453-1997.
[0057] 4. Heat dissipation performance test: Wrap the braided tubing to be tested around a metal mandrel heated by constant power, and apply the rated current to bring the surface temperature of the mandrel to a steady state (100℃). Use thermocouples to measure the surface temperature of the mandrel and the inner and outer surface temperatures of the tubing, and record the temperature difference.
[0058] Table 1 Performance test results of the examples and comparative examples
[0059] This invention produces high-strength, wear-resistant recycled polyester fiber with a breaking strength of 3.5-4.1 cN / dtex, a braided sleeve wear resistance of 2455-2857 cycles (>2000 cycles standard), an air permeability of 168-180 mm / s, and a temperature difference of 8-12K. Its comprehensive performance is superior to that of the comparative examples, and it can meet the requirements of high strength, high wear resistance, and good heat dissipation performance for high-voltage wiring harness braided sleeves in new energy vehicles. At the same time, it realizes the reuse of waste polyester.
[0060] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A high-strength, wear-resistant recycled polyester, characterized in that, The raw materials for preparing the recycled polyester include mercapto-modified polyester, pyromellitic dianhydride, and double bond-modified silica. The mercapto-modified polyester is obtained by modifying waste polyester with a mercaptosilane coupling agent; The double-bond modified silica is obtained by reacting nano-silica modified with an aminosilane coupling agent with an epoxy-containing vinylsilane intermediate; the epoxy-containing vinylsilane intermediate is obtained by reacting vinyltrichlorosilane with glycidol.
2. The high-strength, abrasion-resistant recycled polyester according to claim 1, characterized in that, The mercaptosilane coupling agent is 3-mercaptopropyltriethoxysilane or 3-mercaptopropyltrimethoxysilane.
3. The high-strength, abrasion-resistant recycled polyester according to claim 1, characterized in that, The method for preparing the double bond modified silica includes: (a) Nano-silica was modified with γ-aminopropyltriethoxysilane to obtain amino-modified nano-silica; (b) Reaction of vinyltrichlorosilane with glycidyl ether yields an epoxy-containing vinylsilane intermediate; (c) The epoxy-containing vinyl silane intermediate is reacted with the amino-modified nano silica to obtain double bond modified silica.
4. The high-strength, wear-resistant recycled polyester according to claim 3, characterized in that, The mass ratio of the γ-aminopropyltriethoxysilane to the epoxy-containing vinylsilane intermediate is 1-2:
1.
5. The high-strength, abrasion-resistant recycled polyester according to claim 1, characterized in that, The mass ratio of the mercapto-modified polyester to the double bond-modified silica is 100:1-2.
6. A method for preparing high-strength, abrasion-resistant recycled polyester as described in any one of claims 1-5, characterized in that, Includes the following steps: (1) The waste polyester was placed in a solution containing mercaptosilane coupling agent and reacted. After washing and drying, mercapto-modified polyester was obtained. (2) The mercapto-modified polyester obtained in step (1) is reacted with double bond-modified silica to undergo a mercapto-olefin click reaction to obtain the synthetic polyester; (3) The synthetic polyester obtained in step (2) is mixed with pyromellitic dianhydride, melt-blended and granulated, and then melt-spun, stretched and heat-set to obtain high-strength wear-resistant recycled polyester.
7. The method for preparing high-strength, abrasion-resistant recycled polyester according to claim 6, characterized in that, The mass fraction of the mercaptosilane coupling agent in step (1) is 0.5-2%, the reaction temperature is 60-80℃, and the reaction time is 2-4h.
8. The method for preparing high-strength, abrasion-resistant recycled polyester according to claim 6, characterized in that, The mercapto-olefin click reaction conditions in step (2) are: adding azobisisobutyronitrile and reacting at 75-85℃ for 4-6 hours under nitrogen protection.
9. The method for preparing high-strength, wear-resistant recycled polyester according to claim 6, characterized in that, The temperature of melt blending in step (3) is 250-265℃, the temperature of melt spinning is 270-290℃, and the draw ratio is 2.0-2.4 times.
10. The application of a high-strength, wear-resistant recycled polyester as described in any one of claims 1-5 in the braided sleeve of high-voltage wiring harnesses for new energy vehicles.
Citation Information
Patent Citations
Method for preparing super-hydrophobic textile from thiol-ene click chemistry-modified fiber
CN105696306A
Preparation method of antibacterial modified polyester fiber
CN117904745A
Wear-resistant and tear-resistant foam flame composite fabric and preparation method thereof
CN120382704A